Pengaruh Green Leadership dan Community Involvement terhadap Green Performance Dimediasi oleh Employee Engagement - Synda Lailatus Nadiva; Mulyono Mulyono; Choirul Anam (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The development of sustainable tourism villages requires the implementation of management practices that enhance environmental performance through environmentally oriented leadership, community participation, and stakeholder engagement in achieving sustainability goals. This study aims to examine the influence of green leadership and community involvement on green performance, with employee engagement serving as a mediating variable among the stakeholders and managers of Punten Tourism Village, Batu City. A quantitative approach with an explanatory research design was employed. The study involved all stakeholders and managers of Punten Tourism Village using a saturated sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that green leadership and community involvement have positive and significant effects on green performance. Both variables also significantly enhance employee engagement, which, in turn, positively and significantly influences green performance. Furthermore, employee engagement partially mediates the relationships between green leadership and green performance, as well as between community involvement and green performance. These findings suggest that improving the environmental performance of tourism villages requires the integration of green leadership, active community involvement, and stronger stakeholder engagement to support the implementation of sustainable tourism practices.